Carbon-11 carboxylation of trialkoxysilane and trimethylsilane derivatives using [(11)C]CO(2) - Bongarzone, Salvatore (Royal Society of Chemistry, 2020)

(untitled) (Chem Commun (Camb))
A novel carboxylation radiosynthesis methodology is described starting from cyclotron-produced [(11)C]CO(2) and fluoride-activated silane derivatives. Six carbon-11 labelled carboxylic acids were obtained from their corresponding trimethylsilyl and trialkoxysilyl precursors in a one-pot labelling methodology. The radiochemical yields ranged from 19% to 93% within 12 minutes post [(11)C]CO(2) delivery with a trapping efficiency of 21–89%.